Shadow risks and disasters - Dylan Minor (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2014)
We explore the relationship between incentives and Shadow Risks - those risks that are not easily captured by common financial measures and yet can lead to major adverse events. Theoretically, increased risk-taking is nonmonotonic in higher powered executive compensation. However, for those settings where risky failures are high-stakes - e.g., potential environmental disasters and accounting scandals - the relationship is positive. We test these predictions for environmental and financial accounting failures of large US firms and find that changing CEO equity compensation from 100% stocks to 100% options can increases the odds of an event by 40-60% and the magnitude of such events by over 100%. The effectiveness of policies such as Sarbanes-Oxley and FAS123R in reducing Shadow Risk-taking are discussed.
Keywords: 330; executive compensation; corporate governance; managerial risk-taking; environmental law; accounting law; misconduct; financial crisis